Effect of Inflation and Economic Growth on The Rate of Unemployment - Azaluddin Azaluddin; Lia Hanifa (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
This study aims to determine the effect of inflation and economic growth on the unemployment rate in Indonesia. This research is a quantitative research. Data analysis in this study used multiple linear regression with a random effect model, which was processed using the EViews 10 application. The population in this study was all provinces in Indonesia in 2016-2018. The sample in this study was 34 provinces in Indonesia. The data used in this study is secondary data obtained from the Central Statistics Agency. The results of this study indicate that inflation and economic growth have a negative and insignificant effect on the unemployment rate in Indonesia. Based on the F test and t test, inflation and economic growth variables have no significant effect on the unemployment rate in Indonesia, either partially or simultaneously.